Instructional Strategies that Respond to Global Learners’ Needs in Massive Open Online Courses - Phan, Trang (Online learning (Newburyport, Mass.), 2018)
Massive Open Online Courses (MOOCs) are one of the most innovative forms of online instruction delivered to learners of different language, cultural and educational backgrounds around the world. These multicultural learners have diverse communication styles, learning behaviors and needs that are manifested and demonstrated differently in such a large scale online learning environment as MOOCs. There is little research on how aspects of MOOC learners’ diverse cultural backgrounds and learning behaviors are perceived, how these learners are characterized in terms of their learning needs, and how the MOOC instructors and instructional designers respond to these needs in the course design process. The purpose of this qualitative study was to describe how MOOC learners’ diverse learning needs, stemming from their different language, cultural and educational backgrounds, were perceived and responded to during the course design and delivery. Participants were fifteen instructors and instructional designers in American higher educational institutions who were involved in designing and delivering a wide variety of MOOC subjects on the Coursera hosting platform. The insights of participants into specific instructional strategies that were designed especially for MOOC multicultural learners’ needs were categorized into three themes: language, content and engagement. These strategies aimed to provide support and engage learners with English language barriers, or those who did not have the necessary subject background to keep up with the course, or those who were not familiar with the American education culture. The study also investigated the pedagogical challenges and concerns that the participants faced during and after the delivery of the MOOCs. Typical challenges included confusions caused during the discussion triggered by the subject, the participants’ struggle with the efficiency of peer assessment, and the applicability of the content materials for the global audience.